Artificial Intelligence dan Transformasi Pembelajaran Pendidikan Islam: Peluang, Tantangan Etika, dan Implikasinya: Penelitian - Naila Rahmah Maulidiyah; Lutfiyah Lutfiyah; Ani Cahyadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study discusses Indonesian language and literature learning strategies for developing writing, reading, and creative thinking skills. The literature study method, with thematic analysis, comparative analysis, and narrative synthesis of ten literatures that met the inclusion criteria, was used. The results showed that a combination of thematic, comparative or varied, and innovative or creative learning strategies can improve language skills comprehensively. Thematic strategies facilitate contextual understanding of concepts, comparative and varied strategies encourage active engagement and literacy, while innovative and creative strategies stimulate students' imagination, critical thinking, and creativity. Positive impacts are seen in improving reading skills through text comprehension and vocabulary enrichment, writing skills through creative expression of ideas and coherent writing structures, and creative thinking skills through problem-solving and innovation exercises. Teacher challenges, such as limited media and differences in student abilities, can be overcome by integrating interactive methods, differentiated approaches, and applying best practices from the literature. This study provides practical guidance for teachers to design language and literature learning that is more effective, enjoyable, and relevant to the development of students literacy and creativity.